A new kind of containment : "the war on terror," race, and sexuality - Lugo-Lugo, Carmen R.; Bloodsworth-Lugo, Mary K. (Value Inquiry Book Series, 2009)
This book addresses "containment" as it relates to interlocking discourses around the "War on Terror" as a global effort and its link to race and sexuality within the United States. The project emerged from the recognition that the events of 11 September 2001, prompted new efforts at containment with both domestic and international implications.